Uma abordagem para a priorização de casos de teste de regressão baseada em rastreabilidade - Malimpensa, Gabriel Gioannini (Universidade Federal de São Carlos, 2018)
Context: Build software with quality while respecting cost and time is one of the great challenges of systems development. The requirements traceability and testing activity, such as regression tests, are alternatives to overcome these challenges. However, it is known that the testing activity is very costly and takes too much time for the entire development cycle. Therefore, it justifies the importance of prioritizing test cases, so that the defects are revealed as soon as possible. Objective: The objective of this work was to propose an approach for prioritizing test cases in the context of regression testing, based on traceability. Methodology: A literature review was conducted through a systematic mapping in order to identify the main techniques for prioritizing test cases. It was developed a plug-in for prioritization of test cases based on the proposed approach, for a widely used industry tool (Jira). It was also conducted case studies with real systems to evaluate this approach. Results: The approach elaborated during this work showed good efficacy in the conducted experimental studies. In one of the case studies, the prioritization determined by the approach presented better efficiency than the prioritization manually done by quality analysts and it also was able to find more defects. Conclusions: The obtained results show that the elaborated approach can be an alternative for the application of the prioritization of test cases in the industry.
Keywords: Priorização de casos de teste; Testes de regressão; Rastreabilidade de requisitos; Test case prioritization; Regression tests; Requirements traceability; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO